Hubungan Peletakan Kamera (Angle) dalam Iklan Berbentuk Video - Bobby Halim; Yosef Yulius (Besaung : Jurnal Seni Desain dan Budaya, 2021)
In an advertisement sometimes there is a meaning that is presented not straightforward. Every TVC that uses real human talent cannot be separated from the camera's perspective. THE IMPORTANCE OF CAMERA VIEWS ON VIDEO MEDIA ADVERTISING examines the relationship of camera placement (angle) in influencing the message conveyed by a TVC and how cinematography is used as visual rhetoric. The study was conducted qualitatively with a semiotic film analysis approach. Data THE IMPORTANCE OF CAMERA VIEWS ON VIDEO MEDIA ADS is grouped into 4 structures, namely Visual Structure, Verbal Structure (Language, Character, Settings, Time), Narrative Structure and Audio Structure. Diachronic analysis using signifier (sign) and signified (sign) views. Some types of angles are Extreme Long Shot (ELS), Very Long Shot (VLS), Long Shot (LS), Medium Long Shot (MLS), Medium Shot (MS), Medium Close Up (MCU), Close Up (CU), Big Close Up (BCU), Low Angle Shot, Eye Level Shot. The selection of the selected images to be analyzed is carried out on the following basis: (1) Selecting an image according to the type of camera angle. (2) Sort images according to the type of camera angle. (3) Analyze each film and the impression built from each camera's perspective. (4) Comparing the impressions of the two analyzes. (5) Explain the reasons for the different impressions that arise, when the viewpoint of the camera is the same but the impression obtained is different. The camera angle is important in creating certain impressions, for example the impression of horror.